Nutritional assessment and surgical risk makers in children submitted to cardiac surgery - Leite, Heitor Pons; Fisberg, Mauro; Novo, Neil Ferreira; Nogueira, Eliana Borges Rodrigues; Ueda, lvete Kotomi (São Paulo Medical Journal, 1995)
In order to assess the nutritional status of children with heart diseases and to evaluate nutritional parameters for predicting postoperative complications, 50 children undergoing to cardiac surgery and classified in high and low surgical risk prospectively evaluated. Assessment parameters included anthropometry and plasma proteins albumin, transferrin and prealbumin. The nutritional classification according to Waterlow's modified criteria showed a high prevalence of malnutrition in the population studied (78%). The measures of arm circumference when located below the 5th percentile showed a significant association with general postoperative complications in the high risk group (arm circumference, p = 0,0019; arm muscle circumference, p = 0,0419). The percentage of weight per height, serum albumin and transferrin has not played a prognostic role concerning postoperative morbidity. The mean value of prealbumin was significantly lower in high risk group patients developing postoperative infections (p < 0,01) compared to those who did not. The sensitivity-specificity analysis of prealbumin as risk indicator for postoperative infection was 87.5% and 59% respectively. The nutritional risk classification seems to be a good way to identify the subgroups of children with additional postoperative surgical risk. However, more specific and sensitive tests are desirable to provide an individual identification of these children.